African Trade Unions in Historical Perspective - Bellucci, Stefano (Africana Studia, 2020)
This paper aims to place the history of African trade unions within the broader subject of global labour history. Two assumptions were made. First, trade unions in Africa are formal and usually legal organizations which have historically represented only a minority of African workers, namely wage workers employed in the formal sector. Second, though African trade unions have acted as a progressive force of social change in the beginning of their history they gradually have become a conservative force in politics and society. Drawing from examples from around the continent, the arguments advanced in this paper gravitate around the hypothesis that inumerous labour historians have also made in other parts of the world: trade unions tend to follow the political history of the country in which they operate rather than setting the political agenda. This way, they act within society as mediators between political power and the people they represent. In general, though there have been some exceptions, they do not seek to change the socio-economic system but they do wish to improve it. They are not “revolutionary” forces, despite sometimes claiming to be so. The arguments advanced revolve around three key historical moments: the birth of trade unions, decolonisation and “mass” unionism, and independence and the political dilemmas of trade unions. Keywords: Trade unions, Labour history, Global Labour History, Wage Labour, Capitalism.